Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-24 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Relation of coordination dynamics values to therapy duration for a load of 20N and for exercising in the forward (lines and dots) and backward directions (20Nb; dashed line and crosses) in a patient with a SCI sub C5/6 (Kadri). Note that with no therapy the coordination dynamics values got worse (increased) and upon therapy they improved again. Upon metal removal the coordination dynamics values increased strongly. The transient coordination dynamics value increases (peaks) '1' through '9' fall together with the re-appearance of certain muscle functions or specific improvements of motor and autonomic functions and indicate therefore most likely small bits of regeneration. After the large peak '6' of transient coordination dynamics value increase, urinary bladder functioning was re-learned.